The impact of cone beam computed tomography in diagnosis and endodontic treatment planning decisions - case reports (Research, Society and Development, 2021)
Conventional radiographic techniques have limitations, showing a two-dimensional image of a three-dimensional object, making it difficult to recognize the internal root anatomy in endo-dontic therapy. Cone-beam computed tomography (CBCT) is a diagnostic method that allows the visualization of all structures three-dimensionally, showing promising results compared to periapical radiographs. The objective of this study was to report two clinical cases where CBCT was fundamental to the diagnosis and a better treatment planning of the steps that were taken during the endodontic intervention. The CBCT were performed prior to the treat-ments, the volume of the exams were dynamically analyzed in specific software. The data were interpreted and together with the radiographic image and clinical examination data, the diagnosis and treatment planning were carried out. Given the report and discussion of the two clinical cases, it can be concluded that CBCT proved to be an impacting resource to support diagnosis and decision-making in the treatment of complex endodontic cases. CBCT ensured greater reliability in the diagnosis and treatment plan adopted, increasing the predictability of the endodontic therapy.